The use of paratextual devices in broadcast promotion: a content analysis of season three of Glee on Facebook - Timmons, Rachel, author; Hallahan, Kirk, advisor; Diffrient, Scott, committee member; Martey, Rosa, committee member (Colorado State University. Libraries, 2015)
This study analyzed all Facebook posts during the third season of the Fox Broadcast Network television show Glee (n=763), from August 2011 to May 2012. The study illustrated that Facebook posts can be considered valuable paratextual devices (Gray, 2010b) that can be used in the promotion of a television program. The program’s promoters, who served as Facebook Page administrators, used Facebook for three purposes: build viewership, enhance the live-viewing experience, and build brand awareness and engagement. Visual paratexts, such as images and videos, were used more widely than text-based paratexts. Some of the most frequently employed paratexts included previews/sneak peeks/promos, cast-member specific posts, spoilers or teasers, and music video clips. Posts were about equally split in terms of being related to specific episodes versus the show in general. Almost half of the overall posts displayed high interactivity, which prompted the users to leave the Facebook platform. These posts can be valuable if the show is interested in building brand awareness and enhancing the viewing experience, not just increasing post and Page likes. Surprisingly, posts contained about an equal number of explicit and implicit calls-to-action. Explicitness did not vary based upon the interactivity level, except for low-interactive posts, which had more implicit commands. The average number of Facebook “likes” for a post was roughly 10 times the number of “comments” or “shares,” a finding that was not surprising, because “liking” a post is intrinsically simpler than commenting or sharing. Posts that were episode-specific tended to have more likes, comments, and shares overall. Of those posts that were episode-specific, posts published before and after an episode received more feedback than posts published during an episode. The study also found that longer text could discourage feedback, as posts with longer word counts received fewer likes and comments. In today’s digital world, it is easy for users to access, replicate, and share content. Thus, paratexts become the promotional currency used by promoters and the audiences they enlist to help promote a text. It’s a trend that society can expect to be continued in the context of entertainment television as well as in other cultural and artistic art forms. The research suggests that additional exploration is needed to analyze the role of Facebook (and other social media) in television viewership and engagement. As the television landscape shifts more to the online and mobile realms, advertisers and broadcasters need to understand the effect that social platforms can have on the understanding of the text.